Veritas: a Harvard professor, a con man and the Gospel of Jesus's Wife - Sabar, Ariel (Scribe Publications, 2020)
Intro -- About the Author -- Epigraph -- Title Page -- Copyright Page -- Epigraph -- Contents -- Prologue -- ACT 1 -- SOLICITATIONS -- STRANGE TEACHINGS -- THE HARVARD IMPRIMATUR -- BURNING QUESTIONS -- THE COMPLICATION OF MARY -- A BRILLIANT JEWEL -- AUGUSTINIANUM -- ACT 2 -- EPSILON AND IOTA -- THE KINGDOM OF GOD PUZZLE -- RIDING A TIGER -- ACT 3 -- ACT 4 -- CROSSROADS -- THE LITTLE DARLING AND THE STASI -- HOTWIFE -- DON'T WANT TO KNOW -- THE SECRET ROOM -- INVISIBLE HAND -- FEELING OF CALM -- ACT 5 -- OPERATIONAL EFFECTIVENESS -- THE PRO AND THE CON -- FAUSTIAN BARGAIN -- Epilogue -- Acknowledgments -- Note on Sources and Methods -- Notes -- Selected Bibliography.